MEMAHAMI PENGARUH DIGITAL KNOWLEDGE, PARENTAL SAVING NORMS, DAN SELF-CONTROL TERHADAP FINANCIAL BEHAVIOR PADA GENERASI USIA DEWASA AWAL - Kurniasari, Irma (ANALISIS, 2025)
This study seeks to analyze the influence of digital literacy, parental savings norms, and Self-control on the financial behavior of , early adulthood in Surabaya. The method employed is quantitative, with an explanatory approach, to test and explain the causal relationship between variables through hypothesis testing. The study population consisted of individuals aged 20 to 34, using a purposive sampling technique and a sample size of 100 respondents. Data were collected using a questionnaire and analyzed using path analysis. The results showed that digital financial literacy did not have a significant effect on financial behavior (path coefficient = 0.034; t-statistic = 0.294; p-value = 0.769). In contrast, parental savings norms had a positive and significant effect (path coefficient = 0.322; t-statistic = 4.544; p-value = 0.000), while Self-control was the strongest predictor, positively and significantly influencing financial behavior (path coefficient = 0.524; t-statistic = 6.510; p-value = 0.000). These findings confirm that psychological factors such as Self-control influence financial behavior more than digital literacy alone, and reinforce the role of family financial socialization as a foundation for developing healthy financial behavior.